South-South humanitarianism: The case of Covid-organics in Tanzania. (May 2021) - Richey, Lisa Ann; Gissel, Line Engbo; Kweka, Opportuna L.; Bærendtsen, Pernille; Kragelund, Peter; Hambati, Herbert Qambalo; Mwamfupe, Asubisye
Highlights: Madagascar's gift of Covid-Organics to Tanzania led to reflection on Africa's place in the world. The South-South humanitarian assistance illustrates Tanzania's politics of responding to COVID-19. Covid-Organics demonstrates that South-South humanitarian assistance draws on deep ideologies of pan-Africanism. Traditional remedies like Covid-Organics present a Casablancan vision of pan-Africanism. South-South humanitarian assistance reflects elite politics rather than the distribution of humanitarian goods. Abstract: Tanzania's President sent a plane to Madagascar in May 2020 to bring a shipment of Covid-Organics, a purported cure and prevention for COVID-19. The herbal remedy was described as a gift to help African countries in need. Drawing on preliminary data in English and Kiswahili from unstructured participant observation, social and legacy media available online and shared through contact channels, and ongoing conversations, we explore the Tanzanian policy response to COVID-19. What can the exemplary case of Covid-Organics in Tanzania help us to understand about South-South humanitarian assistance (SSHA) in times of crisis? We suggest that Covid-Organics has enabled the government to project a link to latent debates about Pan-Africanism and Julius Nyerere's legacy and Madagascar's SSHA has provided an opportunity for a public reflection on Africa's place in the world. For some, the remedy's 'Africanness' is its comparative advantage, even promising a continental renaissance. For others, the lack of scientific evidence or approval by global health authorities like WHO is delegitimizing. These findings suggest that receivers of SSHA make sense of it in both a broad, post-colonial discursive context and in a specific context of local contestation. If the promise of this particular form of aid is its ability to transcend deep divisions between North and South, the case of Covid-Organics suggests that SSHA draws on deep ideologies of Pan-Africanism; is increasingly important in crises that are global; and like other forms of humanitarianism, reflects elite politics and priorities rather than prioritizing the distribution of humanitarian goods and decreasing inequality.